ANALISIS MUTU KIMIA DAN ORGANOLEPTIK SNACK BAR DENGAN KOMBINASI TEPUNG JAGUNG KETAN (Zea mays ceratina), TEPUNG HUNKWE DAN JAMBU METE - Ihlana Nairfana (Faculty of Agriculture Science & Technology, 2020)
In Sumbawa, Indonesia, glutinous corns (Zea mays ceratina) are usually sold fresh, unprocessed, or boiled. To increase its shelf life it can be processed into glutinous corn flour. This flour is believed to have many nutrients such as carbohydrates, protein and vitamins. Another agricultural products that are available in abundance in Sumbawa are cashew nuts and green beans, which are also high in nutrients content. The aim of this research is to determine the chemical and sensory characteristics of snack bar made from glutinous corn flour, hunkwe (which is green beans flour) and cashew nuts. The parameter observed was water, ash, protein, carbohydrate and lipid content, and also sensory analysis involved color, flavor, aroma and texture. This is a Completely Randomized Design with 3 different formulations of glutinous corn flour:hunkwe flour in grams; A (200:100), B (150:150) and C (100:200). The data was analyzed using Software SPSS for Analysis of Variance in 5% significance level. The result obtained was there were no significance differences in chemical (proximate) analysis and sensory analysis in snack bar in all three formulations, with an average of carbohydrate content of 57,11 – 57,74 %; protein content of 7,47 – 8,73%; lipid content of 21,24 – 21,53%; water content of 9,88 – 10,85%; and ash content of 2,57 – 2,70%. Panelists overall likes the color, flavor, aroma and texture of the snack bar. Keywords : Snack bar, Glutinous Corn Flour, Hunkwe Flour, Cashew Nut